Effects of Age and Initial Risk Perception on Balloon Analog Risk Task: The Mediating Role of Processing Speed and Need for Cognitive Closure - Koscielniak, Maciej; Rydzewska, Klara; Sedek, Grzegorz (Frontiers in Psychology, 2016)
According to the dual-process theoretical perspective adopted in the presented research, the efficiency of deliberative processes in decision making declines with age, but experiential processes are relatively well-preserved. The age-related differences in deliberative and experiential processes in risky decision-making were examined in this research by applying the Balloon Analogue Risk Task (BART). We analyzed the influence of age on risk acceptance and decision-making performance in two age groups of female participants (younger adults, n = 81; older adults, n = 76), with additional experimental manipulation of initial risk perception. We predicted and confirmed that aging significantly worsens performance on the behavioral BART measures due to age-related decline in deliberative processes. Older participants were found to exhibit significantly higher risk aversion and lower BART performance, and the effect of age was mediated by cognitive (processing speed) and motivational (need for cognitive closure) mechanisms. Moreover, older adults adapt to the initial failure (vs. success) similarly as younger adults due to preserved efficiency of experiential processes. These results suggest future directions for minimizing negative effects of aging in risky decision-making and indicate compensatory processes, which are preserved during aging.